2021
DOI: 10.3390/nano11051185
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Nanostructure in Inkjet Printed Organic Transistors for Pressure Sensing Applications

Abstract: This work reports the development of a highly sensitive pressure detector prepared by inkjet printing of electroactive organic semiconducting materials. The pressure sensing is achieved by incorporating a quantum tunnelling composite material composed of graphite nanoparticles in a rubber matrix into the multilayer nanostructure of a printed organic thin film transistor. This printed device was able to convert shock wave inputs rapidly and reproducibly into an inherently amplified electronic output signal. Var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…A sensitivity of up to 0.48 kPa − 1 was studied and achieved by Lo et al [255]. Griffith et al reported a highly sensitive pressure detector prepared by inkjet printing of electroactive organic semiconducting materials and the detector was able to convert shock wave inputs rapidly and reproducibly into an inherently amplified electronic output signal [256]. Jeong et al manufactured an electromagnetic pressure sensor by printing conductive patterns on a flexible film [257].…”
Section: Pressure Sensorsmentioning
confidence: 99%
“…A sensitivity of up to 0.48 kPa − 1 was studied and achieved by Lo et al [255]. Griffith et al reported a highly sensitive pressure detector prepared by inkjet printing of electroactive organic semiconducting materials and the detector was able to convert shock wave inputs rapidly and reproducibly into an inherently amplified electronic output signal [256]. Jeong et al manufactured an electromagnetic pressure sensor by printing conductive patterns on a flexible film [257].…”
Section: Pressure Sensorsmentioning
confidence: 99%
“…Moreover, OPDs are solution-processable, and the printable electroactive inks enable large-scale, low-cost manufacture on exible substrates. [21][22][23] More signicantly, human tissue has an approximate average density of 1.10 g cm −3 , with so tissues frequently targeted in medical dosimetry having a density of 1.07 g cm −3 . Thus, the density of thin solid lms made from organic electroactive inks is very similar to that of human tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticle-based printing and coating methods are essential for the fabrication of flexible electronic devices comprising several patterns, such as lines and shapes, formed from single or multiple layers. The quality and printability of the pattern are crucial factors affecting the outcomes of printed electronics [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%